Designing & Facilitating Collaborative Learning Networks. A toolkit - Folsom, Amanda (2023)
Collaborative Learning — an approach which brings together people who face common challenges to share knowledge and jointly problem-solve — is a powerful way to support locally-led development and achieve impac t. It provides a structured process in which change agents determine p riorities, set the learning agenda, work together to identify strategi es to address complex challenges, and provide ongoing implementation s upport to one another. Collaborative Learning — unlike traditional app roaches to technical assistance — centers the expertise of local chang e agents and captures the valuable tacit knowledge of practitioners to advance systems change. This toolkit synthesizes lessons, tips, and t ools accumulated from more than a decade of experience designing and f acilitating over 20 Collaborative Learning Networks. The lead author w as Amanda Folsom, Senior Program Director and Collaborative Learning P ractice Lead, Results for Development (R4D). The toolkit benefited fro m the contributions of many R4D colleagues, including Katie Bowman, Ch eryl Cashin, Tanya Jones, Gina Lagomarsino, Agnes Munyua, Maria Jose P astor, and Abeba Taddese. R4D has not done this alone. The lessons and examples are drawn from our work with many network partners from the Joint Learning Network for Universal Health Coverage (JLN), Linked Imm unisation Action Network (Linked), Health Systems Strengthening Accele rator, Strategic Purchasing Africa Resource Center (SPARC), the Primar y Health Care Performance Initiative (PHCPI), the Partnership for Evid ence and Equity in Responsive Social Systems (PEERSS), and the School Action Learning Exchange (SALEX), to name a few. We are grateful for t he thought partnership and support of our partners and funders, includ ing the Bill & Melinda Gates Foundation, Gavi, Hewlett Foundation, Jac obs Foundation, Rockefeller Foundation, USAID, and World Bank.